Co-evolution of antibody lineages and HIV epitopes - Mabvakure, Batsirai Macdonald (My University, 2019)
The HIV envelope glycoprotein (Env) is enormously variable, making it very difficult to represent this diversity in a vaccine. Exposure of the immune system to the continuously diversifying viral quasispecies leads to an “arms race” that contributes to the evolution of the antibody response, and virus escape. Another consequence of this within-host HIV diversity is that viral populations may differ between compartments, with phenotypic effects that may impact the sensitivity of viruses to vaccines/microbicides. The aim of the study is to investigate the role of HIV envelope diversity in driving development of strain-specific or broadly neutralizing (bNAb) responses among hosts, and compartmentalization within hosts, using low-cost computational infrastructure. We first compared viral diversity among hosts by studying eight HIV-1 infected participants who developed bNAbs and six donors who did not develop bNAbs over three years of infection. Defining the viral evolution that contributes to breadth is a major focus of the field so as to elicit bNAbs through vaccination. Comparison of Envs from individuals with bNAbs and strain-specific antibodies revealed that gross evolutionary measures such as Env diversity, evolutionary rates and number of viral infections are not sufficient to distinguish the two groups. However, bNAb donors had more positive selection within targeted sites, with some residues shared between bNAb donors. The positive selection at these common sites increased with the onset of neutralization breadth. The association of shared, positively selected sites with the emergence of breadth highlights the importance of diversity at these positions in bNAb development. We next investigated the viral properties in different compartments within the same individual, as this is important for understanding the potential efficacy of HIV-directed antibodies and microbicides. We compared longitudinal viral Envs between the genital tract and blood plasma of four women. We found evidence of compartmentalization in two of the four individuals. In all four individuals there was restricted viral migration from the genital tract to the systemic blood circulation suggesting a mucosal sieve effect. However, this restricted viral migration was more pronounced in the two individuals who had evidence of compartmentalization. We identified several sites in the Env that differed between viruses in the two compartments, and that arose through positive selection and/or indels. This resulted in charge distribution differences which may differentially impact the sensitivity of these viruses to antibody responses. Overall, these findings show that HIV viruses in the female genital tract may evolve differently from those in plasma, and develop properties that may potentially impact the efficacy of vaccines. These studies relied on high numbers of Env sequences isolated at multiple timepoints, making these analyses computationally intensive. We thus designed and implemented a low-cost bioinformatics cluster for analysing large sequencing datasets (including next generation sequencing). Cluster design included meeting memory requirements, parallelization and long computational times. In addition to supporting viral studies described above, we used the cluster to trace an antibody lineage isolated from an HIV-infected donor, CAP228. The antibody lineage, CAP228-16H/19F, exhibited genetic characteristics similar to the monoclonal antibody, CH58, isolated from the RV144 human vaccine trial. Our analyses identified the unmutated common ancestor (UCA) that initiated the CAP228-16H/19F lineage, and showed that this was derived from a novel allele that encodes an amino acid DDxD motif that was responsible for binding to the V1V2 epitope on Env. This is in contrast to previous studies which suggested that binding was limited to an unusual ED motif that occurs rarely in the immunoglobulin repertoire. The identification of the DDxD motif thus demonstrated that there is a greater potential for eliciting these antibody responses through vaccination as the alleles encoding this motif are common in the population. Overall, this approach to high-performance computing is important as an alternative for data processing challenges faced in low-income communities that are unable to afford advanced computational infrastructure. In conclusion, firstly, these analyses show the importance of diversity at specific amino acid residues in driving bNAb development, which may have valuable implications for vaccination design. Secondly, the study addresses the important subject of whether HIV compartmentalization occurs or not between the female genital tract and plasma, with findings that may impact on vaccine design. Lastly, we demonstrate the development and application of cheaper data processing infrastructure, an approach which may help researchers from low-income settings to overcome challenges in performing computationally intensive analyses.
thesis submitted in fulfilment of the requirements for the degree of Doctor of philosophy (PhD) University of the Witwatersrand, Johannesburg March 2019
Keywords: Antigens CD4; HVI-1